Caries risk and activity in HIV infected children and their controls - Luciana Pomarico; Lívia Ferreira Soares; Alice Kelly; Ivete Pomarico Ribeiro de Souza
Objective: To determine the risk factors and prevalence of caries in HIV infected children (GI) and in children with no evidence ofimmunosupression (GII). Methods: One hundred and thirty-three patients of a Pediatric AIDS Ambulatorial Service in Rio de Janeiro and 85 patients of a Pediatric Dentistry Service were examined. The patients' guardians were interviewed, and provided information about children´s oral higyene, use of medication and dietary habits. The children were examined to determine DMFT and dmft indexes. The Mann-Whitney test was performed at a level of significance of 5%. Results: The two groups (mean age: G1=6.8 years, GII=8.1 years) showed no significant difference in dmft/DMFT indexes (dmft: 6.4 and 8.0; DMFT: 1.0 and 1.4 for GI and GII), but GII showed a higher number of restored teeth (p<0.05). GII showed also a higher frequency of toothbrushing (p<0.05), and in both groups, most of the children brushed their teeth withouth any adult supervision. Sucrose ingestionbetween meals was higher for GI (p<0.05). In GI 78.9% had been using combined antiretroviral therapy and the cariogenic potential of thetherapy administration classified as high was the most frequently observed (45.1%). Significant association was observed only between dmft and sucrose ingestion in GII. Conclusion: GI and GII were exposed to risk factors for a high caries prevalence. The habit of sucrose ingestion between meals was considered an important factor associated with the high prevalence of caries in deciduous dentition in children with no clinical signs of immunosupression.